THE TEST OF ANTIOXIDANT ACTIVITIES WITH COMPARISON OF EXTRACTION METHODS FROM ROBUSTA COFFEE SEEDS (Coffea canephora) - Novi Fajar Utami; Nhadira Nhestricia (Journal of Science Innovare, 2018)
The content of robusta coffee include alkaloids, flavonoids, saponin, tannins, caffeine, and phenol. Differences in the method of extraction of a plant can cause differences in the number of chemical compounds. The purpose of this study was to determine the phytochemical characteristics and antioxidant activity in robusta coffee beans extracted by maceration and sonication method. Antioxidant activity was performed by the method of DPPH (2,2-diphenyl-1-picrylhydrazyl) by spectrophotometry. The results showed that phytochemical characteristics of robusta coffee extract of maceration and sonication contain the same chemical compounds, namely alkaloids, flavonoids, tannins, and saponins. The antioxidant activity of robusta coffee seed extract of sonication result has IC50 of 54,14 ppm which is better than the extract of robusta coffee beans from maceration.